Pleomorphic Xanthoastrocytoma with Oligodendroglioma-Like Areas with Negative 1p19q Co-Deletion - Goel, Deepa; Sharma, Shobhna; Gupta, Aditya (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
The most common mixed glioma encountered in routine surgical practice is oligoastrocytoma (OA); however, its is currently considered a vanishing entity. The 2016 classification of the World Health Organization (WHO) discourages the diagnosis of tumors as mixed glioma. The recommendations are that diffuse gliomas, including those with mixed or ambiguous histological features, should be subjected to molecular testing. Dual-genotype OAs are not yet a distinct entity or variant in the classification. We report a case of mixed glioma: a pleomorphic xanthoastrocytoma (PXA) mixed with an oligodendroglioma. The immunohistochemistry (IHC) pattern of isocitrate dehydrogenase 1 (IDH1) negativity with retained nuclear expression of the alpha-thalassemia x-linked intellectual disability syndrome (ATRX) protein, and 1p19q co-deletion negativity in both the components enabled its identification as a mixed glioma rather than a collision tumor. To the best of our knowledge, the case herein presented is the fourth case of PXA with oligodendroglioma. Out of the other three reported cases, only one was of a collision tumor with a dual genotype, and the other two showed similar molecular signatures in both components. The present article discusses the histological, immunohistochemical and molecular features of the aforementioned case.
Keywords: pleomorphic xanthoastrocytoma; mixed glioma; composite glioma; oligodendroglioma; 1p19q